The effect of coordination, concentration, and motivation on the skills of scoop and chair rhythmic gymnastics on students of sman 39 jakarta - Anik Maryani; Fahmy Fachrezzy; Ramdan Pelana (UNIVERSITAS NEGERI JAKARTA POSTGRADUATE OF PHYSICAL EDUCATION DEPARTMENTS, 2022)
This study aims to determine the direct and indirect effects, as well as the simultaneous effect of exogenous variables with endogenous variables. The research method used is an associative quantitative approach, with test and measurement techniques. Data analysis technique using path analysis approach (Path Analysis). The population in this study is students of XII MIPA / IPS, SMAN 39 Jakarta, as many as 2 classes there are 72 students. The sampling technique in this research is total sampling. So the total sample in this study is 72 people. The instrument variable sensi exercise is measured by the sensi exercise test, the coordination variable used the Focus Light test, the concentration variable was measured by the Concentration Grid Test and the motivation variable is measured by the motivation questionnaire. The results of this study are the direct effect of variable X1 on Y 3 = 1.3% The direct effect of variable X2 on Y = 16.9%. The direct effect of variable X3 on Y 28.8% The direct effect of variable X1 on X3 =38.3%. The direct effect of the X2 variable on X3 is 45.3%. The indirect effect of variable X1 on Y through X3 = 2.076. The indirect effect of variable X2 on Y through X3 is 2.08. Based on the results of the study, it can be concluded that there are direct and indirect effects on the variables of coordination, concentration, motivation on sensi gymnastics.